Elevated odds of metabolic syndrome in psoriasis: a population‐based study of age and sex differences3. (25th December 2014) - Danielsen, K.; Wilsgaard, T.; Olsen, A.O.; Eggen, A.E.; Olsen, K.; Cassano, P.A.; Furberg, A.‐S.
Summary Background Questions remain concerning to what extent age and sex may modify the suggested association between psoriasis and the metabolic syndrome in the general population. Objectives To investigate the association between psoriasis and the metabolic syndrome within a large population‐based cohort by age and sex. Methods A cross‐sectional study including 10 521 participants aged 30–79 years from the Tromsø Study cohort was performed; 1137 participants reported lifetime psoriasis of a mainly mild character. The new harmonized definition of metabolic syndrome was used in the multivariable logistic regression analysis. Results There was a uniformly higher prevalence of metabolic syndrome in men and women with psoriasis compared with those without across all age groups. In women, psoriasis was associated with a 3·8‐times higher odds of metabolic syndrome at age 30 years (95% confidence interval 1·5–9·7), with a decreasing odds ratio with increasing age. In men, psoriasis was associated with a stable 1·35‐times higher odds of metabolic syndrome (95% confidence interval 1·1–1·6) at all ages. Abdominal obesity was the most frequent metabolic syndrome component in women in this study, and there was indication of a dose–response relationship between psoriasis severity, indicated through treatment, and having a high waistline in women. Conclusions This study suggests age and sex variations in the risk of metabolic syndrome among individuals with psoriasis. Given the high prevalence of psoriasis and the significantly elevated burden of metabolic syndrome in this patient group, there may be a benefit from targeted screening of metabolic syndrome among individuals with psoriasis regardless of age and disease severity.